2000
DOI: 10.1634/theoncologist.5-3-238
|View full text |Cite
|
Sign up to set email alerts
|

The Prednisone Dosage in the CHOP Chemotherapy Regimen for Non-Hodgkin's Lymphomas (NHL): Is There a Standard?

Abstract: The Oncologist 2000;5:238-249 www.TheOncologist.com Correspondence: Alvaro Moreno, M.D., F.A.A.P., Division of Hematology/Oncology, The Mayo Clinic, 4500 San Pablo Road, Jacksonville, FL 32224, USA; Telephone: 904-953-7291; Fax: 904-953-2315; e-mail: MorenoAspitia.Alvaro@mayo.edu Received March 16, 2000; accepted for publication May 18, 2000. ©AlphaMed Press 1083-7159/2000 BACKGROUNDOver the last two decades, the incidence of nonHodgkin's lymphoma (NHL) has increased in the U.S. at a rate of 4% per year [1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…This was surprising, and contrary to our a priori assumptions, given the amount of prednisone typically administered with each cycle of CHOP, and the known effect of corticosteroids on appetite. [21]…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising, and contrary to our a priori assumptions, given the amount of prednisone typically administered with each cycle of CHOP, and the known effect of corticosteroids on appetite. [21]…”
Section: Discussionmentioning
confidence: 99%
“…While prednisone (or prednisolone), albeit in variable doses, is the standard corticosteroid in the CHOP regimen [34], primate data has demonstrated that CSF dexamethasone levels are maintained for a longer period than prednisone after equipotent systemic doses [35]. This observation may explain the diminished CNS relapse rate in children with ALL observed with dexamethasone in a randomized comparison with prednisone [36].…”
Section: Discussionmentioning
confidence: 99%
“…Another commonly used first-line regimen is dose-adjusted R-EPOCH (DA-EPOCH-R) which incorporates etoposide and is given as a continuous infusion over 96 hours [3]. While the doses of rituximab and the remaining cytotoxic drugs are fairly standard, the dose of prednisone varies in key clinical trials [4]. Data evaluating the impact of prednisone on outcomes such as hyperglycemia during and after R-CHOP or DA-EPOCH-R chemotherapy are lacking.…”
Section: Introductionmentioning
confidence: 99%